Venture capital versus bank financing in innovative German firms - Dorothea Schäfer; Oleksandr Talavera; Volker Zimmermann (Deutsches Institut für Wirtschaftsforschung (DIW), 2007)
The paper investigates young firms' choice of capital source. Our theoretical model hypothesizes a positive (negative) relation between riskiness of the project (price of venture capital) and receiving informed equity. We test our predictions by employing a unique data set collected by KfW group. The theoretical framework is largely confirmed for the sample of bank financing and independent VC financing. However, the picture is less clear if the sample includes also public and bank-dependent VCs. In this case, empirical evidence is less compatible with theory, in particular the evidence on intrinsic project risk is inconclusive.
Keywords: M13; G32; 330; Equity financing; debt financing; innovation firms; Risikokapital; Fremdkapital; Projektfinanzierung; Unternehmensgründung; Innovation; Deutschland